Advocacy of Midwives Referring Patients for Sectio Caesarea in Second-Level Health Care Provider Social Security Management Agency in Bantul - Yuni Fitriana; Andina Vita Sutanto; Ari Andriyani (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2022)
Some women consider vaginal delivery to be a difficult and dangerous delivery process so that Sectio Cesarea (SC) tends to be chosen even though the SC method has a risk of infection. In the past, SC was still a scary thing, but with midwifery technology the paradigm is starting to shift. Now SC delivery is often an alternative choice of delivery even without medical indication. Midwives cannot refer without medical indication if using BPJS Kesehatan. This qualitative descriptive study with an empirical judicial approach, namely analyzing the trend of increasing SC action in private hospitals, types of medical indications and non-medical indications for SC action, advocacy of midwives in referral of SC patients, and collaboration between midwives and Second-Level Health Care Provider Social Security Management Agency. The results of the SC action study were based on medical indications according to 19 screening for mothers who gave birth to be referred. Children are expensive, cannot stand the pain and can't wait to go through the labor process as a reason for non-medical indications for SC action, Midwives advocate for normal delivery if there is a medical indication that a referral will be made, Midwifery collaboration is carried out according to Social Security Management Agency provisions and there is no fee, except for general patients but it was the doctor who provided not the referral hospital. Midwife advocacy is needed to be able to suppress SC action without medical indication and the Government can improve Social Security Management Agency services to be more integrated.